Exosome-Enriched Plasma Analysis as a Tool for the Early Detection of Hypertensive Gestations - Weingrill, Rodrigo Barbano; Paladino, Sandra Luft; Souza, Matheus Leite Ramos; Pereira, Eduardo Manoel; Marques, Aldilane Lays Xavier; Silva, Elaine Cristina Oliveira; da Silva Fonseca, Eduardo Jorge; Ursulino, Jeferson Santana; Aquino, Thiago Mendonça; Bevilacqua, Estela; Urschitz, Johann; Silva, Jean Carl; et al. (Frontiers in Physiology, 2021)
Hypertensive disorders of pregnancy (HDP) are closely associated with prematurity, stillbirth, and maternal morbidity and mortality. The onset of HDP is generally noticed after the 20th week of gestation, limiting earlier intervention. The placenta is directly responsible for modulating local and systemic physiology by communicating using mechanisms such as the release of extracellular vesicles, especially exosomes. We postulate that an analysis of exosome-enriched maternal plasma provides a more focused and applicable approach for diagnosing HDP earlier in pregnancy. Therefore, the peripheral blood plasma of 24 pregnant women (11 controls, 13 HDP) was collected between 20th and 24th gestational weeks and centrifuged for exosome enrichment. Exosome-enriched plasma samples were analyzed by Raman spectroscopy and by proton nuclear magnetic resonance metabolomics (1H NMR). Principal Component Analysis (PCA) and Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) were used to analyze the Raman data, from the spectral region of 600–1800 cm-1, to determine its potential to discriminate between groups. Using principal component analysis we were able to differentiate the two groups, with 89% of all variances found in the first three principal components. In HDP patients, most significant differences in Raman bands intensity were found for sphingomyelin, acetyl CoA, methionine, DNA, RNA, phenylalanine, tryptophan, carotenoids, tyrosine, arginine, leucine, amide I and III, and phospholipids. The 1H NMR analysis showed reduced levels of D-glucose, L-proline, L-tyrosine, glycine and anserine in HDP, while levels of 2-hydroxyvalerate, polyunsaturated fatty acids, and very-low-density lipoprotein (VLDL) were increased. 1H NMR results were able to assign an unknown sample to either the control or HDP groups at a precision of 88.3% using orthogonal partial least squares discriminant analysis and 87% using logistic regression analysis. Our results suggest that an analysis of exosome-enriched plasma can provide an initial assessment of placental function at the maternal-fetal interface and aid HDP diagnosis, prognosis and treatment, as well as detect novel, early biomarkers for HDP.